Spin-selective chemical reactions in radical pair magnetoreception - Lau, J; Jason Ching Shun Lau (2014)
Many animals on earth need to navigate in their own environments for breeding and foraging. The ability to determine a correct heading and the current location for a migratory bird is critical for its survival. Animals that are sensitive to the Earth’s magnetic field can use it to obtain their direction of travel. In 2000, a paper suggested that radical pair reaction could form the basis for magnetoreception in migratory birds and a flavoprotein, cryptochrome, was proposed as the candidate for the radical pair precursor. Recent in vivo experimental results strongly support the hypothesis that radical pairs formed in the eyes of migratory birds are responsible for their magnetic compass sense. Cryptochrome has also been located in the UV-cones in the retinas of two different species of bird. Radical pairs in living cells are influenced mainly by Zeeman interaction, hyperfine interaction, rotational modulation, etc., and together they influence the recombination reactions of the radical pairs. This thesis considers the possible role of radical pairs in avian magnetoreception, using computer simulations of the quantum mechanical evolution of a radical pair under a variety of conditions. Chapter 1 contains the introductions to spin chemistry, avian magnetoreception, and the mathematical description of the quantum evolution of a radical pair. Chapter 2 describes the four different theoretical models for a general non-diffusion-controlled radical pair reaction and the product yields of a radical pair reaction predicted by these four models are analysed and compared. Chapter 3 introduces a model for avian magnetoreception that integrates photoselection with the radical pair reaction and the model is used to predict the retinal patterns that a bird may be able to use for magnetoreception. The anisotropic singlet product yields of a radical pair comprises the flavin chromophore and the tryptophan of a cryptochrome are also presented in this chapter. A paper based on some parts of this chapter is published [1] in the Journal of The Royal Society Interface. Chapter 4 describes a modified version of an algorithm that is used to calculate the product yields detected in a reaction yield detected magnetic resonance (RYDMR) experiment. The new algorithm is used to analyse the results of two sets of RYDMR experiments in which two radical pair systems, pyrene/1,3-dicyanobenzene and chrysene/1,4-dicyanobenzene, were used. The modulated detection technique used in the RYDMR experiments is also discussed in this chapter. A section of this chapter is published [2] in a paper in the journal Physical Chemistry Chemical Physics. [1] Lau, J.C.S.; Rodgers, C.T.; Hore, P.J., J. R. Soc. Interface, 9 (77): 3329–3337, 2012 [2] Wedge, C.J.; Lau, J.C.S.; Ferguson, K.-A.; Norman, S.A.; Hore, P.J.; Timmel, C.R. Phys. Chem. Chem. Phys., 15 (38): 16043–16053, 2013